Education Management in Multicultural Schools: Building Tolerance and Inclusion - Nurul Fadhilah (Gestion Educativa, 2024)
This research examines educational management strategies in multicultural schools with a focus on building tolerance and inclusion in the educational environment. Multicultural schools face unique challenges in integrating students from different cultural, ethnic and religious backgrounds. This research aims to identify effective managerial approaches in creating an inclusive and tolerant learning environment. Through qualitative methods, data were collected from in-depth interviews with principals, teachers and students in several multicultural schools. The results showed that successful education management in multicultural schools relies heavily on inclusive policies, continuous teacher training and active participation from the school community. The implementation of a curriculum that values cultural diversity and extracurricular programs that promote intercultural interaction were also found to contribute significantly to building tolerance among students. This study suggests that national education policies should further support multicultural schools by providing the necessary resources and guidance to manage diversity. Thus, effective education management in multicultural schools can play an important role in creating a more tolerant and inclusive generation.